Allodynia Is Associated With Initial and Sustained Response to Acute Migraine Treatment: Results from the American Migraine Prevalence and Prevention Study. Issue 7 (11th June 2017) - Lipton, Richard B.; Munjal, Sagar; Buse, Dawn C.; Bennett, Alix; Fanning, Kristina M.; Burstein, Rami; Reed, Michael L.
Abstract : Objective: In a population sample of persons with migraine treating with a single category of acute migraine medication, to identify rates and factors associated with acute treatment outcomes, including 2‐hour pain freedom (2hPF), 24‐hour pain response (24hPR), and 24‐hour sustained pain response (24hSPR). Key predictors include acute treatment type (triptans and other medication categories), the influence of allodynia on response to medication, and the interaction between medication category and presence of allodynia in response to treatment among people with migraine. Background: Cutaneous allodynia was previously associated with inadequate 2hPF, 24hPR, and 24hSPR (sustained response at 24 hours among those with adequate 2hPF) among people with migraine in the American Migraine Prevalence and Prevention (AMPP) Study. Methods: The AMPP Study obtained data from a representative US sample of persons with migraine by mailed questionnaire. The 2006 survey included 8233 people with migraine aged 18 or over who completed the Migraine Treatment Optimization Questionnaire (mTOQ). mTOQ was used to assess acute treatment outcomes including 2hPF, 24hPR, and 24hSPR. Eligible individuals used only a single category of acute prescription migraine treatments (n  =  5236, 63.6%). This sample was stratified into 5 categories of type of acute prescription headache medication used (triptans, nonsteroidal anti‐inflammatory drugs, barbiturate‐combinations, opioids, and opioid combinations and ergot alkaloids). Separate binary logistic regression models evaluated: (1) triptans vs other medication types; (2) presence of allodynia vs no allodynia; and (3) the interaction of medication category with allodynia. Sociodemographic variables, health insurance status, over‐the‐counter and preventive medication use were included as covariates. Odds ratios (OR) and 95% confidence intervals (CI) were generated for each acute treatment outcome. Results: Among eligible participants, the mean age was 46 years, and 82.5% were women. The triptan use group had better outcomes than other medication groups for 2hPF (OR range: 2.00‐2.63, all significant except ergot alkaloids) and 24hPR (OR range: 2.10‐6.22, all significant). No significant medication effects were found for the 24hSPR outcome. The presence of allodynia was associated with significantly worse outcomes for both 2hPF (OR range: 1.42‐1.55, all significant) and 24hPR (OR range: 1.30‐1.32, all significant, except for ergot alkaloids, P  =  .051). Allodynia effects were not significant for the 24hSPR. The interaction between medication and allodynia was also not significant (OR range for 2hPF: .68‐2.02; OR range for 2hPR: .35‐1.34; OR range for 24hSPR: 1.21‐2.72) in any of the models, suggesting allodynia is an important predictor of treatment response regardless of the medication group prescribed. Conclusions: The use of triptan medication was associated with significantly better 2hPF (except vs ergot alkaloids) and significantly better 24hPR outcomes compared with other acute medication categories. The presence of allodynia significantly increased the likelihood of an inadequate treatment response for both of these outcomes. Triptan use was generally associated with the best outcomes. Because allodynia was associated with inadequate outcomes for all medication groups, we suggest that allodynia is an area of unmet treatment need.